The use of songs to increase listening skill among 6th year students at Dorotea Carrion” public school, during the academic period 2013 – 2014 - Collaguazo Narvaez, Jenny Lorena (2016)
This study examined the progress in the development of the listening skill through the use of songs in sixth year student class at Dorotea Carrión public school. A twelve session intervention plan was carried out to improve the skill in the students. A test and a questionnaire were designed to measure the students’ proficiency and perception of the use of songs in the class. A field diary was used to monitor students’ advance regularly. The results indicated that the use of songs facilitated the learning of the listening skill which was reflected in the noticeable increase of the post-test scores. The answers gathered from the questionnaire confirmed the positive attitude toward working with songs. To conclude, this study helped the students to increase their listening skill.